The function of intrinsically disordered region of actin binding protein coronin1 in budding yeast - Han, Xiao (Nanyang Technological University, 2022)
Actin polymerization to filamentous network provides structural basis for multiple biological activities, such as endocytosis, cell migration and intracellular transportation. The diversity of actin filament structures and related cellular functions are dependent on the dynamics reorganization of actin network by a group of actin-binding proteins (ABPs). Coronin is one of the ABPs participating in multiple actin regulation pathways. As a conserved protein family, coronins exist in all eukaryotes and their functions depend on a common three-domain structure: N-terminal β-propeller region is the conserved domain as structural platform for actin-binding, C-terminal coiled-coil region mediates homo-oligomerization, whereas middle region is an intrinsically disordered region (IDR) that is poorly understood. My Ph.D. studies focused on investigation IDR of Saccharomyces cerevisiae coronin1(Crn1). In the first part, we uncovered the role of IDR in regulation of its nearby domains, especially C-terminal coiled-coil domain. Through biochemical and biophysical characterizations, we found IDR is critical for integrity and oligomerization of full-length Crn1 protein by providing two important roles: 1) A flexible spacer between N-terminal and C-terminal. 2) Optimization the oligomerization of coiled-coil domain of Crn1. To evaluate the importance of IDR-guided oligomerization regulation of Crn1, protein engineering combined with biochemical and cell biology experiments were used, which proved tetramer is the optimum functional state of Crn1 both in vivo and in vitro. Further systematic analysis of IDR generated a map displaying a unique pattern of IDR length distribution among coronin protein family, which motivated us to find: 1) Universal necessity of IDR for in vivo localization of coronins. 2) Length of IDR tunes its control to Crn1 oligomerization. The second part talked about phosphorylation regulation of IDR. We firstly identified IDR is the target region of phosphorylation modification by Cdk1 complex in vivo. Through site mutagenesis and NMR spectrometry approach, we uncovered two phosphorylation-dependent regulatory roles of IDR: 1) Phosphorylation enhances structural dynamics of IDR. 2) Phosphorylation modulates in vivo oligomerization and functionality of Crn1. My research provided knowledge for understanding the biological meaning of IDR existence in coronin protein family and shed lights on the importance of structural disorder in regulation of molecular assembly of actin-binding proteins.